Relational Competence, School Adjustment and Emotional Skills: A Cross-Sectional Study in a Group of Junior High School Students of the Sicilian Hinterland - Pellerone, Monica; Razza, Stesy Giuseppa; Miccichè, Sandra; Piccolo, Alessandra Lo (Advances in Social Sciences Research Journal, 2022)
Literature has demonstrated the influence of emotional adjustment toward manifestation of problem behaviors in adolescence above all during the Covid-19 pandemic. The research goal is to investigate the relational competence, the school adjustment and emotional skills in a group of junior high school students of the Sicilian hinterland. The research involved 213 students, among which 82 boys (38.1%) and 131 girls (61.9%), aged between 11 and 14 (M=12.98; S.D.=1.05), of which 6.7% have repeated the school year once. Participants completed following instruments: the Test of Interpersonal Relationships (TRI) developed by Bracken (1993) in order to value the perception of adolescents concerning the quality of their relationships in social, familial and school contexts; the Multidimensional Test of Self-Esteem (TMA) created by Bracken (2003), structured in six scales, which coincide with the dimensions considered constitutive of self-esteem, namely: Interpersonal Relationships, Emotional Competence, Control over the Environment, School Success, Family Life and Body Image Perception. Data show that a good emotional competence of adolescents has a positive influence on learning and scholastic success, but above all on their relational ability towards peer-group.